Changes in the temporomandibular joint disc and temporal and masseter muscles secondary to bruxism in Turkish patients - GARİP, HASAN (SAUDI MED J, 2018)
Objectives: To analyze the relationships between temporalis and masseter muscle hypertrophy and temporomandibular joint (TMJ) disc displacement in patients with severe bruxism using magnetic resonance imaging (MRI). Methods: This retrospective study included 100 patients with severe bruxism, referred to the Department of Oral and Maxillofacial Surgery, University of Marmara and Istanbul Medipol University, Istanbul, Turkey, between January 2015 and December 2016. Patients underwent TMJ MRI with a 1.5-T system in open and closed mouth positions. The masseter and temporalis muscles were measured in the axial plane when the patient's mouth was closed. Results: At its thinnest, the disc averaged was 1.11 +/- 0.24 mm. At their thickest, the masseter averaged was 13.65 +/- 2.19 mm and temporalis muscles was 12.98 +/- 2.4 mm. Of the discs, 24% were positioned normally, 74% were positioned anteriorly, and 2% were positioned posteriorly. The temporalis muscle was significantly thicker in patients with normally positioned discs than in those with anteriorly positioned discs (p=0.035). Conclusions: The temporalis muscle was significantly thicker in patients with normally positioned discs than in those with anteriorly positioned discs (p=0.035). Additional studies should be conducted to evaluate the relationships between all masticatory and surrounding muscles and disc movements in patients with bruxism.
Keywords: DISORDERS; ASSOCIATION; SYMPTOMS; STRESS; SLEEP